Political Branding Strategy Of Rano Karno Through The Tiktok Account @H.Ranokarno During The 2024 Jakarta Regional Election - Muhammad Fatih Al Kautsar; Muhammad Prakoso Aji (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
Political branding has become an increasingly important strategy in digital political communication, particularly on algorithm-driven social media platforms such as TikTok. This study aims to analyze the political branding strategy employed by Rano Karno through the TikTok account @h.ranokarno during the 2024 Jakarta Regional Election campaign. A qualitative approach with a netnographic method was adopted. Primary data were collected through in-depth interviews with five key informants and digital observation of campaign content, while audience responses were examined through the analysis of 1,563 TikTok comments using RapidMiner. The analysis was guided by the Political Branding framework proposed by Pich and Newman (2021), encompassing the dimensions of tangible, intangible, brand trinity, and symbolic communication and trust. The findings reveal that Rano Karno's long-established "Si Doel" persona functioned as the dominant intangible asset, strengthening his emotional connection with audiences while reinforcing Betawi cultural identity through authentic visual representation. The strategy also deliberately reduced the visibility of party branding in favor of strengthening leader branding and delivering policy messages through interactive and entertaining content. Audience comment analysis further indicates that responses associated with the intangible dimension (7.7%) were substantially more prevalent than those related to the tangible dimension (2.2%), highlighting the greater influence of symbolic identity and personal authenticity in shaping public engagement. This study concludes that effective political branding on TikTok depends not only on symbolic communication but also on the authenticity of content and the candidate's ability to adapt personal identity to the communicative culture of the platform, thereby extending the applicability of the Political Branding framework within contemporary digital political campaigns.